Dating Violence and the Impact of Technology: Examining the Lived Experiences of Sorority Members - Emelianchik-Key, Kelly (Violence against women, 2022)
Dating violence (DV) is pervasive on college campuses with far-reaching health implications. We examined 70 sorority members’ lived experiences with DV and explored the role of technology. Experience, perpetration, exposure, support systems, and conceptualization of DV were assessed, and sorority members engaged in small focus groups to examine their lived experiences. Emerging themes included (a) normalization of unhealthy behaviors, (b) technology and the experience of violence, and (c) sources of support and coping. Findings included significant correlations between the experience and perpetration of DV. Results highlight the need for peer intervention and prevention programming and infusing technology in constructive ways.